A Quantitative Assessment of Financial Conditions in Asia - Osorio Buitron, Carolina (IMF Working Papers; Working Paper ;, 2011)
We propose a new Financial Condition Index (FCI) for Asian economies based on two different methodologies: a VAR model and a Dynamic Factor Model. The paper shows that this index has predictive power in forecasting GDP growth and may be thus used as a leading indicator. Based on the FCI, financial conditions in Asia tightened substantially earlier in the global crisis, reflecting losses in the stock markets and tighter credit conditions. In early 2010, financial conditions in Asia recovered rapidly and reached precrisis levels, thanks to accommodative monetary policies and a rapid rebound in regional equity markets.